Public Services At the Minahasa District Education Office - Recky H. E. Sendouw,; Laurens Bulo,; Angel Rumambi,; Meike Imbar,; Vidi Feronika Kapoh, (Technium Social Sciences Journal, 2024)
The aim of this research is to find out and describe public services at the Minahasa Regency Education Office. This research uses qualitative methods, with the process starting from data collection, data reduction, data display and drawing conclusions. Research informants namely; Head of General and Civil Service Subdivision, General and Civil Service Staff, General and Civil Service Staff, and Teachers. Data collection was carried out through observation, interviews and documentation techniques. Data validity checking techniques include the degree of trust, transferability, dependency and certainty. The analysis was carried out using several indicators, namely; 1). Administrative requirements, 2). Systems, mechanisms and procedures, 3). Completion Time, 4). Costs, and 5). Service Complaints Media. The research results show; 1) Administrative requirements have not been maximized because they have not complied with the applicable SKP; 2) Systems, Mechanisms and Procedures: Not yet optimal because even though they comply with the SOP, there are still delays; 3).Completion Time; Not yet appropriate because delays often occur; 4). Management Fees; It is appropriate that there are no fees for processing promotions; 5). Complaint Media Service. Not yet optimal because only a suggestion box is available, not utilizing existing social media/technology.